ELICITATION OF CRITERIA WEIGHTS FOR MULTICRITERIA MODELS: BIBLIOMETRICS, TYPOLOGIES, CHARACTERISTICS AND APPLICATIONS - da Silva, Fabrício Freitas; Souza, Claudio Luiz Melo; Silva, Fábio Freitas; Costa, Helder Gomes; da Hora, Henrique Rego Monteiro; Erthal Junior, Milton (Brazilian Journal of Operations & Production Management, 2021)
Goal: This study aims to review and classify the main methods of criteria weights definition. Design / Methodology / Approach: From a systematized search were articles selected and analyzed, covering a timeline between 1949 and 2020. Results: Fifty sex methods were identified and discussed. Most (49) are subjective, eleven are objectives and three are hybrids. Considering the aggregation procedure, 33 are compensatory and 23 are non-compensatory. Most of the methods are for a single decision maker and just eleven are multidecision makers. The main contributions are published on European Journal of Operational Research journal. Limitations of the investigation: This work does not make a thorough technical analysis of the presented methods and it is not a notebook to indicate to researchers which method is the best for each type of situation. Some methods may not have been included. Practical implications: The selection and the definition of criteria weight is a fundamental question in the Multicriteria Decision Aid (MDCA) approach. The MCDA has a wide application on operation and production management. The diversity of published papers on this subject, the comprehension of its characteristics and applicability is a complex task for researchers and professionals who demand these techniques. Originality / Value: This work contributes to identify the state of the art of the models applied to the weight of the criteria, as well as to identify its characteristics and functionality regarding MCDA modeling.